Dwory biskupów krakowskich w XV w. Przyczynek do rekonstrukcji zaginionej części Liber Benefciorum Jana Długosza - Marciniak-Kajzer, Anna (Acta Universitatis Lodziensis. Folia Archaeologica, 1996)
In 1991 this author published a paper entitled Defensice architecture in the Liber benefciorum of Jan Długosz and archaeological data where all mentions about small fortified residences have been analysed. In this way, three volumes of Długosz’s works published in the 19th century have been examined. In the early 20th century S. Inglot made an attempt to reconstruct the lost first part, which probably was written about 1440 and which contained descriptions of the estates of the bishopric of Kraków with the exclusion of the chapter’s property. References to residences and seats of the bishops are of special interest to the archaeologist. The aim of this article, which is a continuation of the paper mentioned above, was to collect information about the 15th-century seats of the bishops of Kraków. In addition to a few remarks about castles, there was a large group of references to manor-houses usually located in the centres of the estates. A number of references to features defined by S. Inglot as „travelling stations” have also been found. This paper is only a starting-point of further studies of written sources primarily of test excavations of the places described.